Inherited thrombocytopenia caused by ANKRD26 mutations misdiagnosed and treated as myelodysplastic syndrome: report on two cases. (28th October 2017) - Zaninetti, C.; Santini, V.; Tiniakou, M.; Barozzi, S.; Savoia, A.; Pecci, A.
Abstract : Essentials Thrombocytopenia 2 (THC2) is an inherited thrombocytopenia (IT) with dysmegakaryopoiesis. Physicians often do not suspect the genetic origin of thrombocytopenia in patients with THC2. We report two THC2 patients misdiagnosed with myelodysplasia and treated with chemotherapy. IT should be always considered in patients with isolated thrombocytopenia and dysmegakaryopoiesis. Summary: Thrombocytopenia 2 (THC2) is an autosomal‐dominant disorder caused by point substitutions in the 5′UTR of the ANKRD26 gene. Patients have congenital thrombocytopenia, normal platelet morphology and function, and dysmegakaryopoiesis. Thrombocytopenia is frequently discovered only in adulthood and physicians often do not suspect its genetic origin. We describe two unrelated patients referred to two different institutions for investigation of thrombocytopenia. Based on the finding of dysmegakaryopoiesis at bone marrow examination, patients were diagnosed with myelodysplastic syndrome (MDS) (refractory thrombocytopenia) and treated with several courses of 5‐azacytidine. Subsequently, demonstration of thrombocytopenia in their relatives eventually led to molecular diagnosis of THC2 in both families. These cases highlight that patients with THC2 are at risk of being misdiagnosed with MDS and receiving undue myelosuppressive treatments. Because dysmegakaryopoiesis is a feature also of other forms of inherited thrombocytopenia, a genetic disorder must always be considered when a patient presents with isolated thrombocytopenia and dysmegakaryopoiesis.